Nutrition now - Brown, Judith E. (Cengage Learning, 2017)
"Understanding the basic principles of nutrition and its impacts on your health can lead to better choices and more successful diet planning now and throughout your lifetime. Chapters cover nutrition basics such as diet planning, the macronutrients, vitamins and minerals, exercise, pregnancy and lactation, global issues, and much more. Nutrition Now organizes content into easy-to-read, manageable units that help you focus on the concepts while applying what you have learned to your own life"--Provided by publisher.